How to Make The Airline Business Environmentally Friendly - Phaophan, Nattamon (Suan Dusit Graduate School Academic Journal, 2023)
This article aimed to examine the factors that contributed to the environmental impact of the airline business and the processes for resolving pollution problems caused by the airline business. The airline business was the critical transport infrastructure for the country development in economic, social and political aspects to progress and thrive in order to create a better quality of life and promote good relations between countries. Air transport was considered to be more convenient, fast and safe than other forms of transportation, where aircrafts were important for transporting passengers or transporting goods from place to place. Up to now, passenger aircrafts still needed fuel that produced high amounts of carbon dioxide in the air. This turned into pollution that affected the environment and caused inclement weather conditions, resulting in climate change and global warming. In order for those involved to be aware and conscious of the value of resources, and to use the modern technology for the study and development of alternative or renewable energy to reduce air pollution, this can help enable airline business to continue their transportation in a quality and environmentally friendly way.